Female role portrayal in South African magazine advertisements - Juanne Lauer (Communicare)
Even though women actually fulfil many roles in real life, advertisements targeting female consumers are often accused of depicting women in traditionally stereotypical roles. The purpose of this article is to analyse the visual elements of the roles portrayed by female models in South African magazine advertisements. The study on which this article is based has made a unique contribution by investigating not only the relationship between the roles portrayed and the ethnicity of the female models, but also the relationship between the product categories advertised and the ethnicity of the female models. A total of 258 full-page and double-page advertisements were sampled from two issues of nine consumer magazines published in South Africa. The research, using content analysis, found that female models were predominantly portrayed as consumers and as the decorative focal points in advertisements advertising apparel, accessories and personal care products. A significant relationship was moreover identified between the product categories advertised and the ethnicity of the female models